Chemical abundance gradients from open clusters in the Milky Way disk: Results from the APOGEE survey. Issue 8 (30th September 2016) - Cunha, K.; Frinchaboy, P.M.; Souto, D.; Thompson, B.; Zasowski, G.; Allende Prieto, C.; Carrera, R.; Chiappini, C.; Donor, J.; García‐Hernández, A.; García Pérez, A. E.; Hayden, M. R.; et al.
Abstract: Metallicity gradients provide strong constraints for understanding the chemical evolution of the Galaxy. We report on radial abundance gradients of Fe, Ni, Ca, Si, and Mg obtained from a sample of 304 red‐giant members of 29 disk open clusters, mostly concentrated at galactocentric distances between ∼8–15 kpc, but including two open clusters in the outer disk. The observations are from the APOGEE survey. The chemical abundances were derived automatically by the ASPCAP pipeline and these are part of the SDSS III Data Release 12. The gradients, obtained from least squares fits to the data, are relatively flat, with slopes ranging from –0.026 to –0.033 dex kpc –1 for the α ‐elements [O/H], [Ca/H], [Si/H], and [Mg/H], and –0.035 dex kpc –1 and –0.040 dex kpc –1 for [Fe/H] and [Ni/H], respectively. Our results are not at odds with the possibility that metallicity ([Fe/H]) gradients are steeper in the inner disk ( R GC ∼ 7–12 kpc) and flatter towards the outer disk. The open cluster sample studied spans a significant range in age. When breaking the sample into age bins, there is some indication that the younger open cluster population in our sample (log age <8.7) has a flatter metallicity gradient when compared with the gradients obtained from older open clusters.